Adhesion Performance Of Solvent-Based Adhesive In Medical Tube - Ghazali, Muhammad Faris Afdhal (Universiti Sains Malaysia, 2018)
The purpose of this research is to investigate the adhesion performance of solvent-based adhesive in medical tube. Polyvinyl chloride (PVC) in different solvent such as cyclohexanone (CYC), tetrahydrofuran (THF) meythl ethyl ketone (MEK), acetone and xylene were prepared. The effects of different composition PVC/CYC ratios and different solvents are used as the processing parameters to assess the adhesion performance. Five different ratios are selected which are 5:95, 10:90, 15:85, 20:80 and 25:75 for the effect of different composition PVC/CYC ratio whereas for the effect of different solvent, another five different ratios were selected which are 15:85 (PVC/CYC), 15:35:50 (PVC/CYC/THF), 15:35:50 (PVC/CYC/MEK), 15:35:50 (PVC/CYC/acetone) and 15:35:50 (PVC/CYC/xylene). The sample will be characterized in time taken for PVC to dissolved in solvent, and viscosity to correlate the processing parameter and adhesion performance. In this case, the temperature (room temperature) and speed of mechanical stirrer (600 rpm) used is constant. The viscosity and the time taken for PVC to dissolved in solvent were measured as it is postulated that both parameters are the factor that affected the adhesion performance. The adhesion performance was analyzed by using three different tests which are FTIR, lap shear strength test and optical microscopy. FTIR was used in this research to investigate the type of bond and functional group consists in the molecular chain of the adhesive. The shear strength of the adhesive was measured by using lap shear strength test according to ASTM D3163. The morphology study is done via the study of the fracture surface analysis of the all adhesive systems after lap shear test by using optical microscope. The ratios between polymer and solvent also are important as the inter-diffusion of adherend and adhesive depends on the interaction between substrate molecule and adhesive layer. This study highlighted the influence of formulations and processing parameter onto its adhesion performance.